High-density lipoprotein cholesterol, size, particle number, and residual vascular risk after potent statin therapy - Mora, Samia; Glynn, Robert J; Ridker, Paul M (Circulation (New York, N.Y.), 2013)
Chemically measured high-density lipoprotein cholesterol (HDL-C) may not be the best clinical measure of HDL. Little is known about alternative HDL measures such as HDL size or particle number (HDL-P) as determinants of residual risk after potent statin therapy. In Justification for the Use of statins in Prevention: an Intervention Trial Evaluating Rosuvastatin (JUPITER), HDL size and HDL-P were measured by nuclear magnetic resonance spectroscopy, and HDL-C and apolipoprotein A-I (apoA-I) were chemically assayed in 10 886 participants without cardiovascular disease (CVD) before and after random allocation to rosuvastatin 20 mg/d or placebo. Levels were examined with first CVD (n=234). HDL-P correlated better with apoA-I (Spearman r=0.69, P<0.0001) than with HDL-C (r=0.55, P<0.0001). Rosuvastatin lowered low-density lipoprotein cholesterol (49%) and raised HDL-C (6.1%), apoA-I (2.1%), HDL-P (3.8%), and HDL size (1.2%); all P<0.0001. Among placebo-allocated individuals, on-treatment HDL-C, apoA-I, and HDL-P had similar inverse associations with CVD (risk factor-adjusted hazard ratio and 95% confidence interval per 1 standard deviation: 0.79 [0.63-0.98], 0.75 [0.62-0.92], and 0.81 [0.67-0.97], respectively). Among rosuvastatin-allocated individuals, on-treatment HDL-P had a statistically significant and somewhat stronger association with CVD (0.73, 0.57-0.93, P=0.01) than HDL-C (0.82, 0.63-1.08, P=0.16) or apoA-I (0.86, 0.67-1.10, P=0.22). Among rosuvastatin-allocated individuals, on-treatment HDL-P remained significant (0.72, 0.53-0.97, P=0.03) after additionally adjusting for HDL-C. In risk factor-adjusted models, HDL size showed no significant association with CVD. In the setting of potent statin therapy, HDL particle number may be a better marker of residual risk than chemically measured HDL-C or apoA-I. This has potential implications for evaluating novel therapies targeting HDL. http://www.clinicaltrials.gov. Unique identifier: NCT00239681.